Nitrogen and phosphorus nutrition of cattle : reducing the environmental impact of cattle operations (CABI, 2005)
There are benefits to feeding ruminants nitrogen and phosphorus supplements, in terms of milk production and productivity. However, what goes in must also come out. Nitrogen and phosphorus excretions from dairy cattle are a major environmental pollutant. This book describes the latest knowledge in nitrogen and phosphorus nutrition of cattle including requirements, ruminal and total tract metabolism, possibilities of increasing the efficiency of nitrogen utilization and reducing nitrogen and phosphorus excretions from dairy and beef operations. It also includes aspects of the effects of dietary nitrogen and phosphorus on the reproductive efficiency of cattle. This book will be of significant interest to researchers in animal nutrition, animal science and environmental (pollution) science.